Usability and Reliability of Smart Glasses for Secondary Triage During Mass Casualty Incidents - Broach, John (Proc Annu Hawaii Int Conf Syst Sci, 2018)
Wearable smart glasses like Google Glass provide real-time video and image transmission to remote viewers. The use of Google Glass and other Augmented Reality (AR) platforms in mass casualty incidents (MCIs) can provide incident commanders and physicians at receiving hospitals real-time data regarding injuries sustained by victims at the scene. This real-time data is critical to allocation of hospital resources prior to receiving victims of a MCI. Remote physician participation in real-time MCI care prior to victims’ hospital arrival may improve triage, and direct emergency and critical care services to those most in need. We report the use of Google Glass among first responders to transmit real-time data from a simulated MCI to allow remote physicians to complete augmented secondary triage.